Structural and Soil Deformations in Non-Invert and Circular Tunnels: A Centrifuge and Numerical Analysis - Dawood, Abdulaleem; Ueno, Katsutoshi (Salehan Institute of Higher Education, 2025)
Non-invert tunnels are often chosen to reduce initial construction costs compared to circular tunnels, but they frequently require expensive maintenance. Despite their widespread use, limited research has quantified the differences in material requirements (steel and concrete) between these two designs. This study compares the internal forces and material demands of circular and non-invert tunnels using centrifuge model tests and numerical analysis. A combined approach using 40g centrifuge testing and parametric analysis in OPTUM G2 assesses bending moments, lining shear forces, and shear stress distributions. Three tunnel diameters (9 m, 12 m, and 16 m) are analyzed across depth ratios (H/D = 10, 7, 5, and 1), covering eight reinforced concrete lining designs. Results show that circular tunnels have more uniform stress distributions in the lining and surrounding soil, leading to lower bending moments and shear forces. In contrast, non-invert tunnels exhibit stress concentrations near the lower fulcrum corners and spring line. Due to their uniform stress distribution, circular tunnels become more material-efficient than non-invert at greater depths and larger diameters, reducing steel use by up to 36% despite requiring up to 19% more concrete. Non-invert tunnels, however, use less material at shallow depths, saving up to 14% in steel and 23% in concrete.